Лінгвофілософські виміри поняття «Рідна Мова» - Лариса Кравець; Larysa Kravets; Kravec Larissza (II. RF KMF-„RIK-U” Kft., 2020)
Резюме. Проблема визначення поняття «рідна мова» лежить насамперед у площині соціолінгвістики, етнології, педагогіки, психології, проте вона має і широке лінгвофілософське висвітлення. Узагальнення напрацювань в українській та світовій лінгвістиці в найширшому її часово-просторовому й галузевому вияві актуалізує різні питання, пов’язані з рідною мовою, оприявнює суперечності в її трактуванні, встановленні категорійних ознак та функцій. Дискусійним виявляється навіть положення про об’єктивність поняття, оскільки назвати свою рідну мову може тільки сама людина.

Abstract. The article describes the philosophical study of the phenomenon of "native language". The concept of “native language” is ambiguous and diverse. This encourages philosophers and linguists to look for its stable differential features. In Ukrainian philosophy, the concept of “native language” approaches the concept of “nation” and acquires political significance. This understanding of the concept of "native language" was formed primarily on the basis of the ideas of German classical philosophy. О. Potebnya developed these ideas in East Slavic science in the 19th century. The native language played an important role in the formation of the Ukrainian nation in the 19th - early 20th centuries. In the post-Soviet period, the concept of “native language” was again updated. Modern researchers describe the concept of “native language” as a volatile phenomenon, depending on subjective and objective factors, but it remains relevant in the aspect of building a national state.
https://kmf.uz.ua/wp-content/uploads/2020/11/final-baleczky_kotet_2020-10-28.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00008462
Keywords: рідна мова; лінгвофілософія